Emotional and Mental Wellbeing Following COVID-19 Public Health Measures on People Living With Dementia and Carers. (May 2022) - Hanna, Kerry; Giebel, Clarissa; Tetlow, Hilary; Ward, Kym; Shenton, Justine; Cannon, Jacqueline; Komuravelli, Aravind; Gaughan, Anna; Eley, Ruth; Rogers, Carol; Rajagopal, Manoj; Limbert, Stan; et al.
Background: To date, there appears to be no evidence on the longer-term impacts caused by COVID-19 and its related public health restrictions on some of the most vulnerable in our societies. The aim of this research was to explore the change in impact of COVID-19 public health measures on the mental wellbeing of people living with dementia (PLWD) and unpaid carers. Method: Semi-structured, follow-up telephone interviews were conducted with PLWD and unpaid carers between June and July 2020. Participants were asked about their experiences of accessing social support services during the pandemic, and the impact of restrictions on their daily lives. Results: 20 interviews were conducted and thematically analyzed, which produced 3 primary themes concerning emotional responses and impact to mental health and wellbeing during the course of the pandemic: 1) Impact on mental health during lockdown, 2) Changes to mental health following easing of public health, and 3) The long-term effect of public health measures. Conclusions: The findings from this research shed light on the longer-term psychological impacts of the UK Government's public health measures on PLWD and their carers. The loss of social support services was key in impacting this cohort mentally and emotionally, displaying a need for better psychological support, for both carers and PLWD.